Radar Belt for the Visually Impaired - Dave, Derrick Jeremiah; Ahmad, Ida Laila; Masnani Mohamed (Evolution in Electrical and Electronic Engineering, 2023)
A person who is partially blind finds it difficult to maintain daily activity, and many challenges arise when they are moving from one location to another. The most crucial one is recognizing obstructions while they are moving. They frequently run into poles, walls, cars, and other road users because they are unable to see, which can cause severe injuries. Therefore, it is crucial to introduce portable devices to assist this group by being able to provide the appropriate information, at the appropriate location, in the appropriate manner. Electronic travel aids (ETAs) have become more common and have excelled at helping the sight handicapped navigate. The methodology used to implement an ultrasonic sensor system that helps visually impaired people navigate unfamiliar environments safely is presented in this research. The aim of this study is to develop a more efficient tool for visually impaired persons. The system reacts to nearby obstacles by using ultrasonic sensors and generates vibration using a vibrating motor belt to achieve high performance, low power consumption, and portability. The final section, reports the experimental findings from fifteen (15) persons under situations with various barriers. These outcomes demonstrate good performance and participant acceptance, emphasizing the simplicity of following instructions and the brief training period.